Potassium deficiency causes more nitrate nitrogen to be stored in leaves for low-K sensitive sweet potato genotypes - Liu, Jingran; Xia, Houqiang; Gao, Yang; Pan, Dongyu; Sun, Jian; Liu, Ming; Tang, Zhonghou; Li, Zongyun (Frontiers in Plant Science, 2022)
In order to explore the effect of potassium (K) deficiency on nitrogen (N) metabolism in sweet potato (Ipomoea batatas L.), a hydroponic experiment was conducted with two genotypes (Xushu 32, low-K-tolerant; Ningzishu 1, low-K-sensitive) under two K treatments (-K: <0.03 mM K+ and +K: 5 mM K+) in the greenhouse of Jiangsu Normal University. The results showed that K deficiency decreased root, stem, and leaf biomass by 13%-58%, and reduced whole plant biomass by 24%-35%. Compared to +K, the amount of K and K accumulation in sweet potato leaves and roots were significantly decreased by increasing root K+ efflux in K-deficiency-treated plants. In addition, leaf K, N, ammonium nitrogen (NH4+-N) or nitrate nitrogen (NO3–N) in leaves and roots significantly reduced under K deficiency, and leaf K content had a significant quadratic relationship with soluble protein, NO3–N or NH4+-N in leaves and roots. Under K deficiency, higher glutamate synthase (GOGAT) activity did not increase amino acids synthesis in roots; however, the range of variation in leaves was larger than that in roots with increased amino acid in roots, indicating that the transformation of amino acids into proteins in roots and the amino acid export from roots to leaves were not inhibited. K deficiency decreased the activity of nitrate reductase (NR) and nitrite reductase (NiR), even if the transcription level of NR and NiR increased, decreased or remained unchanged. The NO3-/NH4+ ratio in leaves and roots under K deficiency decreased, except in Ningzishu 1 leaves. These results indicated that for Ningzishu 1, the relative more NO3- was stored under K deficiency in leaves, and the NR and NiR determined the response to K deficiency in leaves. Therefore, the resistance of NR and NiR activity to K deficiency may be a dominant factor that ameliorates the growth between Xushu 32 and Ningzishu 1 with different low-K sensitivities.